The Teachers' and Students' Perceptions of the Need for Integrated Contextual Sustainability Biology Worksheets - Firgi Dama Julia Sari; Novy Eurika; Ika Priantari (UNIVERSITAS KHAIRUN, 2026)
Biology instruction on the topic of environmental change holds great potential for integrating sustainability contexts as part of efforts to support Education for Sustainable Development (ESD). However, the limited availability of teaching materials that have not yet incorporated sustainability contexts poses a significant challenge to instruction. This study aims to determine teachers’ and students’ perceptions regarding the need for Biology worksheets integrated with sustainability contexts, particularly in the topic of environmental change. This study employs a quantitative approach using a survey method. The study’s respondents consisted of three high school Biology teachers and 63 eleventh-grade students. Data were collected through questionnaires and analyzed descriptively. The results indicate that the instructional materials currently in use are still dominated by textbooks and worksheets focused on conveying concepts and have not been integrated with sustainability contexts. This situation impacts students’ understanding, as they have not fully connected the material to environmental issues within a sustainability context. Teachers and students share the same perception regarding the need to develop contextual Biology teaching materials that incorporate sustainability. Based on the needs analysis, there is a need to develop Biology teaching materials integrated with sustainability in the context of environmental change to support the implementation of ESD.